Anti-Phishing Techniques in Cryptography - Akshey Nanda; Himanshu Gupta (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Phishing is a process in which Phishers try to leak out the credentials of users by hosting a fake web page on user's browser. To save users from phishing attacks, many researchers have dug deep and presented their insights. Nowadays, in the era of 21st century,  banks are using the OTP and visual cryptography for the authentication of both sides i.e. user and the bank. In this paper, we are proposing a methodology in which a user will need to give his finger prints as an authentication.